Keanekaragaman Budaya Menjadi Basis Pembelajaran BIPA - Moh. Muzakka Mussaif (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Learning of BIPA in Indonesia most still use conventional ways, i.e. still competency-based aspects of the competence of the language plus the introduction of the culture of Indonesia. Learning is thus deemed less effective and boring because each teacher just reachs appropriate syllabus target competencies. To solve the issue is needed learning of BIPA integrative methods. Although a teacher only tasked to teach one of several aspects of linguistic competence, but if using this method of integrative learning will accelerate mastery of the language of Indonesia while its culture for learners. Such learning methods can be carried out with thematic learning-based material culture.